Effect on liver function of an ayurvedic medicine Punarnavasava after 28 days chronic toxicity studies on male Sprague Dawley rats - Parvin, Afrin; Azad, M. Al; Sarker, Arjyabrata; Khan, M. Abu Adnan; Jahan, Nusrat; Nadvi, M. Rohan; Ahmmed, M. Masum; Choudhuri, M. S. K. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Punarnavasava (PVR) is an ayurvedic formulation predominantly used as a traditional medicine in the rural population to get relief from edemic conditions. Though this medication is recognized as generally safe, clinical research on this formulation is scarce. Therefore, contributing to determining the safety of this drug may help ensure safer treatment for thousands of patients. Methods: The effect of chronic administration of PVR on liver function was determined by administrating chronically to the male Sprague-Dawley rats at a dose of 40 ml per kg body weight for 28 days. In this experiment plasma protein, albumin, serum bilirubin and various serum enzymatic parameters were determined. Results: In the study, the total protein content in the plasma was increased (11.05%) in the PVR treated male rats. The increase in total protein was not statistically significant but was noticeable (p=0.104). On contrary, the albumin content was decreased (7.92 %) in PVR treated male rats and it was not statistically significant, yet it was noticeable (p=0.076). No difference on the bilirubin level between the control and the experimental group was noted. In the PVR administered male rats, activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and alkaline phosphatase (ALK-P) was decreased by 31.90%, 45.44%, 82.82% and 32.53% respectively and all these changes were statistically very highly significant (p=0.0001) for all these enzymes. In contrast, a not significant negligible increment was observed in the GGT activity. Conclusions: From this study, it is evident that there was no adverse increase in the liver function parameters in the male rats after chronic administration of PVR, on the contrary significant decrease in the serum liver function enzymes were noted, therefore, it can be concluded that this Asava preparation (PVR) can be administered chronically. With the slight increase in GGT though negligible suggests caution for use in pregnancy related edemic conditions which may deteriorate liver cholestasis related to later stage of pregnancy. Further research should be done to reconfirm the safety of this ayurvedic medicine in pregnancy.